PERAN ARTIFICIAL INTELLEGENCE DALAM SISTEM INFORMASI MANAJEMEN - Ahmad Nurkholis; Ines Heidiani Ikasari (AI dan SPK : Jurnal Artificial Intelligent dan Sistem Penunjang Keputusan, 2023)
Abstract This research examines the implementation of artificial intelligence (AI) in the context of management information systems (MIS). The main objective of this research is to describe how AI can be used in management information systems to increase efficiency, productivity, and make better decisions. Artificial intelligence is a branch of computer science related to the development of computers or machines that can imitate human expertise in carrying out certain tasks. . In the context of management information systems, AI can be used to automate business processes, analyze large amounts of information quickly and accurately, and provide valuable predictions and advice for decision making. This research relates to a comprehensive analysis of the literature on the application of AI in MIS. The results show that AI can be applied to various aspects of SIM, including information collection and analysis, inventory management, supply chain management, customer service personalization, and strategic decision making. The advantages of using AI in SIM include increasing process speed and accuracy, saving budgets, improving quality decision making, as well as improving user experience. However, there are also challenges that need to be overcome, such as adequate availability of information, security and privacy of information, and sufficient description of methods for integrating AI into existing SIMs. In this research, several steps that can be taken to implement AI in SIMs are proposed. efficiently. This includes selecting AI methods that match business needs, gathering and sterilizing relevant information, developing appropriate AI models, engaging users in the development and use of AI systems, and measuring and managing AI performance continuously. Overall, this research shares a better description of the capabilities of implementing AI in SIM as well as sharing instant guidance for organizations looking to adopt this technology. It is hoped that by using AI in SIM, organizations can achieve greater efficiency, better productivity and smarter decision making.